First record of Prabhergia Salmon (Collembola: Tullbergiidae: Tullbergiinae) in the Neotropics with a description of a new species from Brazil - Mendonça, Maria Cleide De; Signes, Tatiana Cristina Da Silveira (Zootaxa, 2024)
The genus Prabhergia Salmon, 1965, known so far only in Asia, is recorded for the first time in Brazil. This genus is characterized especially by presence of pseudocelli along the tergites; postantennal organ arranged in two rows with 3 and 4 vesicles respectively (originally listed as 3-5 vesicles in each row), sensory organ of antennal segment III with two sense clubs, robust, exposed and facing each other on the anterior surface, and a single sense club, robust and exposed, on the posterior surface, furca absent and anal spines present. The new species Prabhergia mana sp. nov. is described based on specimens found in bee nests in the ground in the Botanical Garden, city of Rio de Janeiro, Rio de Janeiro state.